Characterization of volatile compounds from processed pineapple waste by Static Headspace Gas Chromatography-Mass Spectrometry (SHS GC-MS/MS) - Ravichandran, Chandrakala; Upadhyay, Ashutosh; Khan, Zober Alam; Aggarwal, Manjeet; Singh, Rakhi (Journal of Postharvest Technology, 2020)
The volatile compounds from processed pineapple waste (PPW) from two common cultivars of pineapple in India (Queen and King) were studied  using Static headspace Gas Chromatography-Mass Spectrometry (SHS-GC-MS/MS). From the processed waste of Queen cultivar, a total of about  55 to 60 volatile compounds were identified; majorly esters (Methyl 2-methyl butyrate (50%), Methyl butyrate (9%), Ethyl 2-methyl butyrate (6%) and  methyl hexanoate (2%), followed by terpenes and a few alcohols, alkanes, aldehydes, acids, lactones and other classes of compounds in minor  quantities. From processed waste of King cultivar, a total of 60 to 65 volatile compounds were identified; again majorly esters (Methyl hexanoate (27%)  followed by methyl butyrate (18 %) and methyl 2-methyl butyrate (15%), methyl octanoate (4%) in addition to terpenes, alcohols, alkanes, aldehydes  and other classes of compounds present in minor concentrations. The study indicated that volatile compounds of pineapple waste was quite  comparable to that of the pineapple juice and has the potential for utilization.
Keywords: Processed pineapple waste; static headspace; gas chromatography; volatile compounds; queen cultivar